2006
DOI: 10.1136/ard.2006.051979
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokines and steroidal hormones in polymyalgia rheumatica and elderly-onset rheumatoid arthritis

Abstract: Different cytokine and steroidal hormone patterns suggest that patients with PMR and those with EORA/PMR seem to be have a more intensive inflammatory reaction and are more efficient responders to glucocorticoid treatment than patients with EORA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
1
9

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 32 publications
5
54
1
9
Order By: Relevance
“…In PMR patients, elevated blood levels of IL-6, which were markedly decreased following glucocorticoid treatment, were found not only in our study, but also in several other studies (26)(27)(28)(29). Interestingly, it has been reported that plasma IL-6 levels rapidly return to increased levels following brief withdrawal of prednisolone treatment (27), suggesting that the underlying cause of the high IL-6 production in PMR is not eliminated in parallel with clinical remission induced by prednisolone.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In PMR patients, elevated blood levels of IL-6, which were markedly decreased following glucocorticoid treatment, were found not only in our study, but also in several other studies (26)(27)(28)(29). Interestingly, it has been reported that plasma IL-6 levels rapidly return to increased levels following brief withdrawal of prednisolone treatment (27), suggesting that the underlying cause of the high IL-6 production in PMR is not eliminated in parallel with clinical remission induced by prednisolone.…”
Section: Discussionsupporting
confidence: 61%
“…The importance of IL-1␣/␤, IL-1Ra, IL-8, MCP-1, and TNF␣ in PMR is a subject of controversy, with differing reports on the blood levels of these cytokines and chemokines (26,28,29,(31)(32)(33). Interestingly, IL-1 receptors have been found to be overexpressed in the muscle nuclei and sarcolemma of patients with polymyositis and dermatomyositis, and it is possible that IL-1 impairs muscle fiber function by mechanisms other than muscle fiber damage (34).…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealing age-related reduction of DNA methylation of the TNF promoter suggest that age-related loss of the epigenetic signature of this cytokine may contribute to inflammaging and contributing to the pathogenesis of late onset rheumatic diseases such as PMR and RA in which this cytokine has been shown to a pivotal mediator of chronic inflammation [24,25].…”
Section: Discussionmentioning
confidence: 80%
“…Increased serum concentrations of proinflammatory cytokines, including IL-1ß, TNF-α, and IL-6, in patients with PMR have been reported, but no elevation of IL-1ß or TNF-α was found in other reports 1,2 . Only IL-6 has been observed to be consistently high in patients with active disease [4][5][6] . IL-6 is recognized as the most sensitive indicator of disease activity and course and therefore IL-6 inhibition with tocilizumab may constitute a novel strategy for treatment of PMR.…”
Section: To the Editormentioning
confidence: 99%